AB0634 FINDINGS OF EXERCISE ULTRASOUND CARDIOGRAPHY IN PRE-PAH PATIENTS WITH SYSTEMIC SCLEROSISARE CORRELATED WITH EXTENT OF CAPILLARY LOSS DETECTED BY NAILFOLD VIDEOCAPILLAROSCOPY. (June 2019) - Ashihara, Konomi; Fukaya, Shusaku; Naganawa, Tatsuaki; Hoshino, Meiko; Kato, Yasuchika; Yoshida, Shunji; Yasuoka, Hidekata
Abstract : Background: Systemic sclerosis (SSc) is characterized by excessive fibrosis, injuries in vasculature, and production of autoantibodies (1). Patients with SSc are complicated with various organ involvements, which can give a great impact on their prognosis (2). Of these, pulmonary arterial hypertension (PAH) is one of leading causes of death and the determinant of prognosis in SSc (3). And early diagnosis is an important key to improve their prognosis. The nailfold videocapillaroscopy (NVC) is a non-invasive modality which can evaluate the status of microvasculature of patients with SSc. However, the significance of NVC in patients with "pre-clinical" PAH was unclear. Objectives: To examine the significance of detection of microvascular injury by NVC in patients with pre-clinical PAH patients with SSc. Methods: Patients with SSc who newly visited the outpatient clinic at Fujita Health University Hospital between august 2015 to March 2016 were consecutively involved. All the patients fulfilled the 1980 preliminary classification criteria for SSc (4). The diagnosis of PAH was based on the definition in 2015 ESC/ERS guideline. The NVC (Medcap®3.0, DS MEDICA) was used to detect microvascular change and average capillary density and the number of capillaries/view were calculated. Also, existence of giant capillaries, hemorrhage and patterns of capillary changes were also documented. Transthoracic ultrasound cardiography (UCG) was performed using iE33 with 5MHz sector probe S5-1 (Philips). Exercise loading was done with an ergometer (Lode). Ejection fraction, E/e', velocity of tricuspid regurgitation jet (TR jet), tricuspid annular plane systolic excursion (TAPSE) were examined in a supine position. Tricuspid regurgitation pressure gradient (TRPG) was calculated using velocity of TR jet based on Bernoulli principle. Exercise loading was started at 25 Watt, and then increased 25 Watt every 3 minutes and TRPG at maximum exercise was also calculated. Parameters of NVC were compared with those of UCG. Patients with "pre-clinical" PAH were defined as patients 1) asymptomatic, 2) who did not meet the definition of PH by right heart catheterization (RHC), 3) whose probability of PH is lower than "intermediate" by UCG, 4) who did not see any UCG signs for PH based on the guideline and 5) who did not have severe interstitial lung disease, especially% FVC> 70% and/or area of ILD based on CT scan was <20% of the entire lung field. Results: Nineteen patients with SSc were newly visited. Male to female ratio was 4:15, mean age 63 ± 13 years, and mean disease duration was 138 ± 109 months. Ratio of limited skin type was 79%. 37% were with ILD and 11% were with PAH confirmed by RHC. There is no correlation between TRPG at rest and the density of capillaries. However, there is a significant, negative correlation between TRPG at exercise and the capillary density (r = 0.57, P < 0.02). Furthermore, the same result was observed even with seventeen "pre-PAH" cases (r = 0.67, P < 0.04). Conclusion: Our study suggests that the finding of NVC, especially the extent of capillary loss, is correlated with disease process of PAH, even subclinically, and may predict the progression to PAH in SSc. Since NVC is non-invasive, NVC can detect earlier PAH candidates and contribute to the improvement of prognosis. References: [1] Denton CP, et al. Trends Immunol2005; 26: 596. [2] Steen VD, et al. Ann Rheum Dis2007; 66: 940. [3] avouac J, et al. J Rheumatol2010; 37: 2290. [4] the Subcommittee for Scleroderma Criteria of the american Rheumatism association Diagnostic and therapeutic Criteria Committee. Arthritis Rheum1980; 23: 581. Disclosure of interests: None declared